Trust dan Akuntabilitas dalam Kepemimpinan Bencana: Analisis Perbandingan Perspektif Al-Qur'an dan Administrasi Publik atas Pengunduran Diri Kepala Daerah di Aceh - Rahmat Hidayat (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2026)
The resignation and public declarations of incapacity by several regional heads during the flood and landslide disasters in Aceh generated widespread debate concerning the ethical responsibilities of public leaders in times of crisis. While administrative studies generally evaluate such events through procedural accountability and institutional performance, limited attention has been given to the Qur'anic conception of leadership accountability as a moral and spiritual obligation. This study aims to examine the concepts of trust (amānah) and accountability in the Qur'an and compare them with modern administrative accountability in interpreting the resignation of regional heads during disaster management in Aceh. Employing a qualitative library research design, the study adopts thematic Qur'anic interpretation (tafsīr mawḍūʿī) integrated with comparative analysis of public administration literature, classical and contemporary Qur'anic exegesis, and relevant scholarly works on leadership and disaster governance. The findings demonstrate that Qur'anic accountability extends beyond procedural and institutional obligations by integrating moral integrity, continuous leadership presence, justice, and transcendental responsibility before Allah. In contrast, administrative accountability primarily emphasizes legal compliance, organizational performance, and political responsibility. The comparative analysis reveals that the resignation or withdrawal of regional leaders during disaster emergencies represents not only an administrative deficiency but also a violation of the Qur'anic principles of amānah and moral leadership. This study contributes theoretically by proposing an integrated framework of Qur'anic and administrative accountability that enriches contemporary discussions on disaster leadership and offers an ethical foundation for strengthening accountable public governance in Muslim societies.